Severe ischaemic cardiogenic shock with cardiac arrest and prolonged asystole: a case report. Issue 3 (27th July 2018) - Strangl, Felix; Schwarzl, Michael; Schrage, Benedikt; Söffker, Gerold
Abstract: Background: Extracorporeal life support (ECLS) by veno-arterial extracorporeal membrane oxygenation (VA-ECMO) is a valuable treatment option during severe cardiogenic shock and during cardiac arrest unresponsive to conventional management. It is applied to bridge the first critical days until the patient recovers or a destination therapy is established. 1 Prolonged episodes without cardiac electrical activity during VA-ECMO are a major problem, as they may cause pulmonary oedema and severe left ventricular (LV) thrombosis. 2 Here, we report a case of a 50-year-old man who presented with a 30-h episode of complete absence of electromechanical activity during ECLS and finally recovered with favourable neurological outcome. Case summary: A 50-year-old man with out-of-hospital cardiac arrest was transferred to a peripheral hospital after initial successful cardiopulmonary resuscitation (CPR). In the emergency room, he presented with ST-segment elevation myocardial infarction and cardiogenic shock with third-degree atrioventricular block. After immediate insertion of a temporary pacemaker, he received percutaneous coronary intervention of the left anterior descending artery and the circumflex artery. Due to worsening cardiogenic shock, ECLS with VA-ECMO and an Impella ® pump was established. Cumulative time of CPR (out of hospital and in hospital) was 41 min. After transfer to our institution's intensive care unit, both the heart's mechanical and electrical activity ceased for more than 24 h and recovered slowly thereafter. After showing promising neurological outcome, epicardial pacemaker leads, an implantable cardioverter-defibrillator, and finally, a LV assist device were implanted. He was dismissed into rehabilitation with only minor neurological residua 6 weeks later. Discussion: Impella ® implantation on top of VA-ECMO may be considered beneficial in the therapy of prolonged cardiac arrest. 3 While VA-ECMO ensures oxygenation and organ perfusion, Impella ® vents the left ventricle and enhances coronary perfusion. In the presented case, a favourable outcome was reached despite an 'untreated' prolonged absence of cardiac electromechanical activity. Under specific circumstances during ECLS with extracorporeal membrane oxygenation and Impella ®, waiving of temporary pacing may be considered in absent cardiac electromechanical activity to avoid further complications.